2019
DOI: 10.1021/acs.jpcb.9b02682
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights into the Layered Microstructure and Time-Dependent Stability of [BMIM][PF6] Confined within the Meso-Slit of Carbon

Abstract: Clarifying the microstructures and time-dependent stability of ionic liquids (ILs) within the confinement of the meso-slit of carbon is the first step to understand the intrinsic synergy effect between ILs and a promising mesoporous carbon electrode. In this work, we adopted molecular dynamics to systematically investigate the behavior of [BMIM]­[PF6] in the 2.8 nm-wide meso-slit of carbon. The confined ILs formed a pronounced layered spatial distribution and can be divided into three distinct regions, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
3
7
0
Order By: Relevance
“…8). The observed three distinct layers agreed well with a recent simulation findings, in which, the slits confined IL exhibits an apparent triple layered spatial distribution [69].…”
Section: Layering Structured Ils At the Interfacessupporting
confidence: 92%
“…8). The observed three distinct layers agreed well with a recent simulation findings, in which, the slits confined IL exhibits an apparent triple layered spatial distribution [69].…”
Section: Layering Structured Ils At the Interfacessupporting
confidence: 92%
“…In our previous work, for fluid microstructures in the graphene slit, we found that the H‐bond density of fluid molecules is inhomogeneous 63 . The heterogeneous H‐bond structure near the interface may lead the friction coefficient to present a nonlinear change for glycerol aqueous solutions within graphene slits.…”
Section: Resultsmentioning
confidence: 92%
“…In our previous work, 38 we found that the nanoconfined imidazole-type IL, ([BMIM][PF 6 ]), can exhibit a pronounced layered spatial distribution. The characteristic orientations of the imidazole rings of ILs in the region nearest to the solid surface are considerably different from those in other regions.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
“…The carbon atoms in the graphene walls and the titanium and oxygen atoms in the rutile(110) walls were modeled as rigid LJ spheres. The carbon parameters of graphene 38,45 and the titanium parameters and the oxygen parameters of rutile(110) walls 46,47 are shown in Table 2. These parameters were the same as those in our previous works.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation